We have the function f(x) = x + 1

Now f(x) + f(y) = 7

=> x + 1 + y + 1 = 7

=> x + y = 5 ...(1)

f(x) + 2*f(y) = 12

=> x + 1 + 2y + 2 = 12

=> x + 2y = 9 ...(2)

(2) - (1)

=> y = 4

substitute y = 4 in (1)

=> x + 4 = 5

=> x = 1

**Therefore x = 1 and y = 4.**

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now